Extracellular Vesicles As Modulators of Tumor Microenvironment and Disease Progression in Glioma - Mondal, Abir; Kumari Singh, Divya; Panda, Suchismita; Shiras, Anjali (Frontiers in Oncology, 2017)
Diffuse gliomas are lethal tumors of the Central Nervous System (CNS) characterized by infiltrative growth, aggressive nature and therapeutic resistance. The recent 2016 WHO classification for CNS tumors categorizes diffuse glioma into two major types that include IDH wild-type glioblastoma, which is the predominant type and IDH-mutant glioblastoma which is less common and displays better prognosis. Recent studies suggest presence of a distinct cell population with stem cell features termed as glioma stem cells (GSC) to be causal in driving tumor growth in glioblastoma. The presence of a stem and progenitor population possibly makes glioblastoma highly heterogeneous. Significantly, tumor growth is driven by interaction of cells residing within the tumor with the surrounding milieu termed as the tumor microenvironment. It comprises of various cell types such as endothelial cells, secreted factors and the surrounding extracellular matrix which altogether help perpetuate the proliferation of GSCs. One of the important mediators critical to the cross-talk are extracellular vesicles (EVs). These nano-sized vesicles play important roles in intercellular communication by transporting bioactive molecules into the surrounding milieu, thereby altering cellular functions and/or reprogramming recipient cells. With the growing information on the contribution of EVs in modulation of the tumor microenvironment, it is important to determine their role in both supporting as well as promoting tumor growth in glioma. In this review, we provide a comprehensive overview of the role of EVs in tumor progression and glioma pathogenesis.